DODOL KEDONDONG SEBAGAI SOUVENIR KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU RIAU - Salsa Ulfa Armis; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This writing recommends to describe the process of making, packaging and carrying out the promotion of dondol kedondong which is a typical souvenir of Rengat District, Indragiri Hulu Regency. This research uses descriptive qualitative method, the research subjects are owners of the dodol kedondong KUBE Rendri industry, dodol kedondong traders and buyers of dodol kedondong. Data collection is done by observational studies, in-depth interviews and documentation. Analysis of the data used in this study, namely data reduction, data presentation and conclusions.Kedondong Dodol as a typical souvenir Rengat District Indragiri Hulu Regency is the right thing. Visitors are very satisfied with the dodol kedondong because it has good taste, the right texture, arouse the appetizing aroma, attractive color and practical packaging. The appropriate price and location of sales makes it easy for visitors to buy dondol kedondong products. Promotion has also penetrated the internet media so that dodol kedondong is slowly known by the wider community.Keywords: Dodol Kedondong, Souvenirs, KUBE Rendri